TINJAUAN PERJANJIAN BAKU PADA KONTRAK BERLANGGANAN INDIHOME PT TELEKOMUNIKASI INDONESIA TBK - Nanda Khairunnisa; Ambar Budhisulistyawati (Fakultas Hukum Universitas Sebelas Maret, 2026)
PT Telkom’s Indihome subscription contract is a standard form contract made by one of the leading parties where the other parties by no means have to follow the contract without having any chance to alter the provision under the proposed agreement by both parties. The purpose of this article is to understand the practice of subscription contract by Indihome, whether it is already conducted in accordance to the fundamental of legal agreement or not. This article is done by normative law approach which is prescriptive. Types of data being used in this article are primary, secondary, and tertiary data gathered through document and library study by Cyber Media. Deductive method was used to analyse the case. The result shows that Indihome’s subscription contract did not meet the valid terms of agreement, which is statedt fee in Article 1320 of the Civil Code. Indihome’s contract contains an exoneration clause that contradicts Article 18 of the Consumer Protection Act.